Harry Potter and the order of the phoenix - Rowling, J. K.; Bloomsbury Publishing (London : Bloomsbury, 2004)
Harry Potter, now a fifth-year student at Hogwarts School of Witchcraft and Wizardry, struggles with a threatening teacher, problematic house elf, the dread of upcoming final exams, and haunting dreams that hint toward his mysterious past.
Sequel to: Harry Potter and the Chamber of Secrets.
Keywords: Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Fiction; Large print books; Magic -- Fiction; School stories; Wizards -- Fiction; England -- Fiction